The Lysosomal Protein Arylsulfatase B Is a Key Enzyme Involved in Skeletal Turnover. (24th August 2018) - Pohl, Sandra; Angermann, Alexandra; Jeschke, Anke; Hendrickx, Gretl; Yorgan, Timur A; Makrypidi‐Fraune, Georgia; Steigert, Anita; Kuehn, Sonja C; Rolvien, Tim; Schweizer, Michaela; Koehne, Till; Neven, Mona; et al.
ABSTRACT: Skeletal pathologies are frequently observed in lysosomal storage disorders, yet the relevance of specific lysosomal enzymes in bone remodeling cell types is poorly defined. Two lysosomal enzymes, ie, cathepsin K (Ctsk) and Acp5 (also known as tartrate‐resistant acid phosphatase), have long been known as molecular marker proteins of differentiated osteoclasts. However, whereas the cysteine protease Ctsk is directly involved in the degradation of bone matrix proteins, the molecular function of Acp5 in osteoclasts is still unknown. Here we show that Acp5, in concert with Acp2 (lysosomal acid phosphatase), is required for dephosphorylation of the lysosomal mannose 6‐phosphate targeting signal to promote the activity of specific lysosomal enzymes. Using an unbiased approach we identified the glycosaminoglycan‐degrading enzyme arylsulfatase B (Arsb), mutated in mucopolysaccharidosis type VI (MPS‐VI), as an osteoclast marker, whose activity depends on dephosphorylation by Acp2 and Acp5. Similar to Acp2/Acp5 –/– mice, Arsb‐deficient mice display lysosomal storage accumulation in osteoclasts, impaired osteoclast activity, and high trabecular bone mass. Of note, the most prominent lysosomal storage accumulation was observed in osteocytes from Arsb ‐deficient mice, yet this pathology did not impair production of sclerostin (Sost) and Fgf23. Because the influence of enzyme replacement therapy (ERT) on bone remodeling in MPS‐VI is still unknown, we additionally treated Arsb ‐deficient mice by weekly injection of recombinant human ARSB from 12 to 24 weeks of age. We found that the high bone mass phenotype of Arsb‐deficient mice and the underlying bone cell deficits were fully corrected by ERT in the trabecular compartment. Taken together, our results do not only show that the function of Acp5 in osteoclasts is linked to dephosphorylation and activation of lysosomal enzymes, they also provide an important proof‐of‐principle for the feasibility of ERT to correct bone cell pathologies in lysosomal storage disorders. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.